(untitled) (Proceedings of the International Conference on Public Health, 2017)
Drugs and food which marketed in Indonesia must meet quality and safety requirements that are regulated by NADFC-RI. A Survey of Indonesian Public Awareness Index on Drugs and Food was conducted in 2016 with the objective of obtaining Public Awareness Index score in National scale. The Public Awareness Index is a measure (on a 100 / likert scale) that explains the level of public awareness in understanding, acting, and in the daily behavior of choosing and consuming drugs and food products. The sampling methodology used census blocks with home visit techniques in the survey area of 15 Provinces and a total of 5,240 household respondents. The Respondents are the general public at selected location with at least 15 years of age. Using approach of the Knowledge, Attitude & Perception, Practice Study to get information about people’s knowledge, attitude and behavior in choosing drugs and food including traditional medicines, cosmetics and food supplements. Measurement of index survey was conducted using questionnaires that were delivered face to face and the data analysis statistically used SPSS. The study resulted the value of the Public Awareness Index on Drugs (Ethical and Antibiotics) = 65.78, Other Drugs (Traditional medicine and Vitamin) = 49.23, Cosmetics = 71.54 and Processed Food = 75.36. Overall, it can be concluded that Indonesian Public Awareness Index was at a score of 65.48. This position shows the public has been GOOD ENOUGH consciousness in choosing and consuming drugs, traditional medicine, cosmetic and food products.